Clinical, Economic, and Humanistic Impact of Short-Bowel Syndrome/Chronic Intestinal Failure in Portugal (PARENTERAL Study) - Silva,Raul (2023)
Abstract Introduction: This study aimed to assess the clinical, economic, and humanistic impact of short-bowel syndrome/chronic intestinal failure (SBS/CIF) in Portugal. Methods: This is a retrospective multicenter cohort chart review study, with a cross-sectional component for quality-of-life (QoL) evaluation. Inclusion criteria comprised patients with SBS/CIF, aged ≥1 year, with stable parenteral nutrition (PN). Data collection included patient chart review over a 12-month period and patient/caregiver self-report and SF-36/PedsQL™ questionnaires. Main endpoints comprised clinical and PN characterization, healthcare resource use (HRU), direct costs, and patient QoL. Results: Thirty-one patients were included (11 adults and 20 children). Patients’ mean age (standard deviation [SD]) was 57.9 (14.3) years in adults and 7.5 (5.0) years in children, with a mean time since diagnosis of 10.2 (5.9) and 6.6 (4.2) years, respectively. PN was administered for a mean of 5.2 and 6.6 days/week in adults and children, respectively; home PN occurred in 81.8% of adults and 90.0% of children for a mean of 9.6 and 10.8 months/year, respectively. The mean annual number of hospitalizations was 1.9 and 2.0 which lasted for a mean of 34.0 and 29.4 days in adults and children, respectively. Twenty-one and forty hospitalization episodes were reported in adults and children, respectively, of which 71.4% and 85.0% were due to catheter-related complications. Mean annual direct costs per patient amounted to 47,857.53 EUR in adults and 74,734.50 EUR in children, with PN and hospitalizations as the main cost-drivers. QoL assessment showed a clinically significant impaired physical component in adults and a notable deterioration in the school functioning domain in children. Conclusion: In Portugal, SBS/CIF patient management is characterized by a substantial therapeutic burden and HRU, translating into high direct costs and a substantial impairment of the adults’ physical function and children’s school functioning.